PEMETAAN JALUR PENDAKIAN GUNUNG SAGO MELALUI NAGARI SIKABU – KABU DENGAN METODE PARTISIPATIF UNTUK PENGEMBANGAN EKOWISATA MINAT KHUSUS - ahmad asriful fauzi; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
ABSTRACT The research aims to determine the mapping of the water resources, Shalter and Mount Sago climbing routes for the development of Ecotourism special interest in climbing. This research approach is quantitative descriptive, where quantitive research will produce descriptive data. Descriptive research is a study conducted to know the value of independent variables, Either one or more variables (independent) without making comparisons, or linking with other variables. This research uses participatory methods of data collection, which is putting the community as the main perpetrator in this research. This research uses FGD to get an agreement with the community regarding the process of obtaining research results. The results of this study are an alternative map of sago hiking trails through Nagari Sikabu-Kabu. This alternative line has a length of 4.6108 km with 2 water sources and 2 shalters.